Will COVID-19 change the calculus of climate policy? - Thomas F. Rutherford; Christoph Böhringer (ZBW - Leibniz Information Centre for Economics, 2021)
Public health experts caution that global warming increases the likelihood of novel coronaviruses and amplifies their impacts. Such contagions are virtually unique in their ability to inflict catastrophic worldwide harm. Even more alarming is the forecast that future coronavirus pandemics will be more frequent and potent. If the public comes to recognize that the pain and suffering they are currently experiencing are but another symptom of global warming, the motivation for urgent action to limit temperature rise may reach a tipping point. Navigating the current situation will require considering both existential threats jointly. Here, we present results from an integrated assessment model adapted to examine the implications of current and future pandemics for climate policy. We find that the threat of pandemics can lead to tighter temperature targets than might otherwise be justified. In a world of shrinking economic resources for reducing harm to public health and wellbeing, global warming and pandemics must be recognized as interconnected threats.
Keywords: C61; D61; Q54; 330; COVID-19; climate change; integrated assessment